Jenis–Jenis Teripang (Holothuroidae) di Perairan Kampung Auki Distrik Padaido Kabupaten Biak Numfor, Papua - Bia C. Pallo; Nikki Lewaherilla (Jurusan Biologi FMIPA Universitas Cenderawasih, 2011)
Sea cucumber is one of important commodity in Papua. Beside play role as protein source, sea cucumber also important cosmetic ingredient. Despite Papua has rich in sea natural resources, until now still lack of information on diversity of sea cucumber in Papua, therefore, this study aim to identify the species and diversity of sea cucumber of one of sea cucumber in sea water of Auki island. The study has conducted during March–April 2010. Transect line was used in this study. Data were collected from 3 station, five transect lines were placed at each station. Abiotic factors such as salinity, temperature and pH of sea cucumber habitat were also collected during the study. Diversity index was calculated by using Shannon-Wienner formula. It was found that index of diversity sea cucumber (H) at 0.23. Sea cucumber species found were Actinopyga lecanora, Actinopyga miliaris, Bohadschia similis, Bohadschia marmorata, Bohadschia vitiensis, Holothuria scabra, Holothuria scabra var versicolor, Holothuria atra, Holothuria argus dan Holothuria coluber. Key words: Species diversity, Sea cucumber commodity, Auki Island.